Proceedings of the 2017 ACM Conference on Innovation and Technology in Computer Science Education 2017
DOI: 10.1145/3059009.3059040
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking in Italian Schools

Abstract: In this paper the rst two years of activities of "Programma il Futuro" project are described. Its goal is to disseminate among teachers in Italian primary and secondary schools a be er awareness of informatics as the scienti c basis of digital technologies. e project has adapted Code.org learning material and has introduced it to Italian schools with the support of a dedicated web site. Response has been enthusiastic in terms of participation: in two years more than one million students have been engaged and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…It is almost equal in elementary school; then the number of girls involved in competitions concerning first and second grade of secondary school drastically decreases. These results are similar to those found in another, independent MIUR initiative to promote Informatics and computational thinking [2].…”
Section: Ops and Gendersupporting
confidence: 90%
“…It is almost equal in elementary school; then the number of girls involved in competitions concerning first and second grade of secondary school drastically decreases. These results are similar to those found in another, independent MIUR initiative to promote Informatics and computational thinking [2].…”
Section: Ops and Gendersupporting
confidence: 90%
“…We believe these elements, while of course shared with other disciplines or very general, must be understood inside the discipline of CS; otherwise, as stated by Voogt et al (2015), this "runs the risk of diluting the idea of CT, blurring and making it indistinct from other 21st century skills". For example, Corradini et al (2017a) found that teachers saw the value of a nation-wide "coding" project more in fostering transversal competencies or domain-general skills (like promotion of awareness and comprehension of problem solving, logical thinking, creativity, attention, planning ability, motivation for learning, student interest, cooperation) than in teaching CS core concepts. The same sample (Corradini et al, 2017b) struggled to give a sound and complete definition of CT, focusing on some crucial aspects like problem solving, mental processes, and logic, but often forgetting to refer in any way to an informationprocessing agent.…”
Section: Elements Of Ctmentioning
confidence: 99%
“…The project has adapted Code.org learning material and has introduced it to Italian schools with the support of a dedicated web site, featuring also an introduction to CT. Response has been enthusiastic in terms of participation: in the first two school-years (2014-15 and 2015-16) more than one million students have been engaged and have completed a total of 10 million hours of informatics in schools [6].…”
Section: Introduction 1contextmentioning
confidence: 99%